2017
DOI: 10.1111/and.12885
|View full text |Cite
|
Sign up to set email alerts
|

Do penile haemodynamics change in the presence of hydrogen sulphide (H2S) donor in metabolic syndrome-induced erectile dysfunction?

Abstract: Erectile dysfunction (ED) is defined in relation to the metabolic syndrome (metS). Hydrogen sulphide (H S), a gasotransmitter, has been revealed to get involved in hypertension, insulin secretion and regulation of vascular tone especially in erectile physiology. This study aimed to investigate the effect of H S on metS-induced ED. Animals were divided into two groups as control and metS, which were fed with standard diet or 60% high-fructose diet for 10 weeks respectively. The metS model was evaluated with bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…We demonstrated that H 2 S production in penile tissues of rats with hyperlipidemia-associated ED was decreased, and STS treatment could alleviate the change. Similar to our findings, decreased H 2 S generation in penile tissues was accompanied by impaired erectile function, indicating the importance of H 2 S in maintaining sexual function [24,25]. Our results also indicated that the expression of CSE and CBS was decreased in the HFD group, and STS treatment increased expression of these two H 2 S-generating enzymes, which can account for the H 2 S production changes.…”
supporting
confidence: 90%
“…We demonstrated that H 2 S production in penile tissues of rats with hyperlipidemia-associated ED was decreased, and STS treatment could alleviate the change. Similar to our findings, decreased H 2 S generation in penile tissues was accompanied by impaired erectile function, indicating the importance of H 2 S in maintaining sexual function [24,25]. Our results also indicated that the expression of CSE and CBS was decreased in the HFD group, and STS treatment increased expression of these two H 2 S-generating enzymes, which can account for the H 2 S production changes.…”
supporting
confidence: 90%
“…H 2 S concentration was measured in plasma and heart tissue via methylene blue as-say as described previously [ 28 , 29 ]. To assess H 2 S production, 75μL of plasma combined with 500 μL of reaction mixture containing 0.1 mol/L potassium phosphate buffer (325 μL), substrate, and cofactor of H 2 S that are l -cysteine and pyridoxal-5-phosphate, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that, besides tissue enzymes, the gut microbiota-derived H 2 S may be involved in the development of hypertension [83,89,96]. In addition, H 2 S donors were found to relax corpus cavernosum and were tested for the treatment of erectile dysfunction [97][98][99][100].…”
Section: H 2 S In the Cardiovascular Systemmentioning
confidence: 99%